Discovery and rediscoveries of Golgi cells - Galliano, Elisa (Blackwell Science Inc, 2010)
When Camillo Golgi invented the black reaction in 1873 and first described the fine anatomical structure of the nervous system, he described a ‘big nerve cell’ that later took his name, the Golgi cell of cerebellum (‘Golgi'schen Zellen’, Gustaf Retzius, 1892). The Golgi cell was then proposed as the prototype of type-II interneurons, which form complex connections and exert their actions exclusively within the local network. Santiago Ramón y Cajal (who received the Nobel Prize with Golgi in 1906) proceeded to a detailed description of Golgi cell morphological characteristics, but functional insight remained very limited for many years. The first rediscovery happened in the 1960s, when neurophysiological analysis in vivo revealed that Golgi cells are inhibitory interneurons. This finding promoted the development of two major cerebellar theories, the ‘beam theory’ of John Eccles and the ‘motor learning theory’ of David Marr, in which the Golgi cells regulate the spatial organisation and the gain of input signals to be processed and learned by the cerebellar circuit. However, the matter was not set and a series of pioneering observations using single unit recordings and electron microscopy raised new issues that could not be fully explored until the 1990s. Then, the advent of new electrophysiological and imaging techniques in vitro and in vivo demonstrated the cellular and network activities of these neurons. Now we know that Golgi cells, through complex systems of chemical and electrical synapses, effectively control the spatio-temporal organisation of cerebellar responses. The Golgi cells regulate the timing and number of spikes emitted by granule cells and coordinate their coherent activity. Moreover, the Golgi cells regulate the induction of long-term synaptic plasticity along the mossy fibre pathway. Eventually, the Golgi cells transform the granular layer of cerebellum into an adaptable spatio-temporal filter capable of performing several kinds of logical operation. After more than a century, Golgi's intuition that the Golgi cell had to generate under a new perspective complex ensemble effects at the network level has finally been demonstrated.